Docg iconography: methods and hypotheses for a systematic analysis of the visual identity of wine consortia - Polidoro, Piero (E|C, 2020)
The purpose of this article is to outline the method of analysis of a research on the visual identity of the Italian DOCG wine consortia and to test the underlying hypotheses on a restricted corpus. The purpose of the general research will be to identify, through qualitative and quantitative analysis, recurrences in the logos representing wine consortia. The preliminary work was carried out by creating an analysis sheet of the visual characteristics of the brands, which was applied to the DOCGs of the two most renowned wine-producing regions in Italy: Piedmont and Tuscany. A form was compiled for each brand and this comparative observation made it possible to hypothesize a system that accounts, through a few positions, for almost all the brands observed. Particular attention was paid to color values and the way in which they represent one of the fundamental oenological oppositions: that between white wines and red wines.